INTEGRASI NILAI-NILAI ISLAM DAN PRINSIP PENDIDIKAN GLOBAL DALAM PROSES PEMBELAJARAN DI SMP IT AL-IRSYAD AL-ISLAMIYYAH KARAWANG - Tauhidah, Vicka; Achmad Junaedi Sitika; Agus Susilo Saefullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education based on Islamic values ​​needs to be integrated with global educational principles to develop a superior generation. This study aims to determine the application of Islamic values ​​in learning activities at SMP IT Al-Irsyad Al-Islamiyyah Karawang, identify its integration with global educational principles, and assess the impact of religious activities on student character development. The research method used participatory observation of morning and evening dhikr activities, congregational prayer, halaqah (Islamic circle), the habit of wearing Islamic dress, and the Quran memorization program. The results indicate that the integration of Islamic values ​​with global educational principles creates a balance between students' spiritual, emotional, and intellectual intelligence. Students develop characters of faith, noble character, discipline, collaboration, and openness to the world. These findings emphasize the importance of developing interactive and collaborative learning methods that instill Islamic values ​​and 21st-century competencies. Recommendations for this study include increasing the integration of spiritual values ​​in learning, developing interactive methods, and collaborating with schools, teachers, parents, and the community to shape students' holistic character.